Risk factors associated with atherogenic dyslipidemia in the presence of optimal statin therapy. (1st December 2017) - Zhao, Wang; Zheng, Xi-Long; Jiang, Ze-Nan; Liao, Xiao-Bo; Zhao, Shui-Ping
Abstract: Background: This study investigated the prevalence of atherogenic dyslipidemia (AD) in Chinese outpatients whose low-density lipoprotein cholesterol (LDL-C) levels reached the goals with statin monotherapy and evaluated the characteristics of these patients. Methods: An analysis of the Dyslipidemia International Survey-China study that was carried out at 122 hospitals in China. Among patients reaching their LDL-C goals, the presence of AD was defined as triglyceride levels ≥ 1.7 mmol/L and/or low levels of high-density lipoprotein cholesterol (men: < 1.0 mmol/L; women: < 1.3 mmol/L). Results: 22, 039 patients receiving statin monotherapy were analyzed. According to the American National Cholesterol Education Program Adult Treatment Panel III, 13, 088 patients reached LDL-C goals, and 7134 patients of them had AD. Age, male gender, BMI, sedentary lifestyle, diabetes mellitus, ischemic cerebrovascular disease, serum uric acid levels, and fasting plasma glucose (all P < 0.05) were independently associated with AD. Based on the Chinese guideline for the management of dyslipidemia, 13, 551 patients reached LDL-C goals, and 7719 patients of them had AD. Age, male gender, BMI, sedentary lifestyle, coronary heart disease, serum uric acid levels, and fasting plasma glucose (all P < 0.05) were independently associated with AD. The intensity of statin therapy did not affect the prevalence of AD. Conclusion: There was a high prevalence of AD in Chinese patients with optimal statin treatment. Some risk factors associated with AD were identified, but these factors were slightly different according to two criteria/guidelines. The intensity of statin therapy did not reduce the prevalence of AD. A combination lipid therapy may be more suitable for Chinese patients.